SOME PRINCIPLES FOR TERMINOLOGISTS. - Kohler, E. L. (The Accounting Review, 1935)
Abstract Definition in its popular sense is the process of delimiting a concept or thing with the object of establishing that usage for a word or phrase, which has significance common to all persons. Definition is also popularly understood to be the expression through which the limits of the concept or thing are set up. Without definition, or with more than a single definition in common use, situations frequently arise where no exact medium of communication exists. Probably every person has had the experience of participating in protracted disputatious only to discover in the end that he and his opponent had been talking different languages. Within the realm of logic, definition has as its purpose the determination of the qualities of universals. Hence it may be said that the necessity of a common language and the necessity of building up an adequate background for the introduction of logical principles place upon one as accountants the burden of exploring thoroughly the requirements of good definition.